Penilaian terhadap kesuksesan organisasi sosial keagamaan: Studi kasus pada organisasi ‘aisyiyah - Muhammad Ghazali Bagus Ani Putra (INNER: Journal of Psychological Research, 2022)
The purpose of this study was to assess the success of the ’Aisyiyah organization as a socio-religious organization. The research method used is a mixed method, namely a qualitative approach as the main method and a quantitative approach as an additional method. The qualitative method uses instrumental case studies. Collecting qualitative data using field notes on ’Aisyiyah’s charities, inquiries on the achievements of religious social organizations and interviews with some of ’Aisyiyah’s administrators. This study involved seven participants as central, regional, regional, branch and branch administrators. The qualitative analysis used is thematic analysis. While the quantitative method in this study used a questionnaire on the perception of organizational success of ’Aisyiyah in three groups, namely administrators, members and students of ’Aisyiyah. The total respondents involved were 1,090 people. The quantitative analysis used in this study was a one-way ANOVA. The results showed that ’Aisyiyah met the indicators of success of socio-religious organizations based on preliminary studies. In addition, all groups of respondents have the same perception of the success of ’Aisyiyah. The implications of further research are discussed. Keywords: assessment, success of socio-religious organizations